Penyelenggaraan Makanan, Tingkat Kecukupan Energi dan Status Gizi pada Siswi SMP - 'Ain, Kasyful; Prameswari, Galuh Nita (HIGEIA (Journal of Public Health Research and Development), 2020)
Abstract According to the Regulation of the Minister of Health of the Republic of Indonesia Number 75 of 2013, the AKG needed by girls aged 13-15 years is 2000 kcal. Efforts to meet the energy needs and good nutrition of children through consumption in schools can be done through the provision of food in schools. The purpose of this study was to analyze the implementation of food in the dormitory and determine the level of energy sufficiency and nutritional intake of female students living in the boarding school. The research method is descriptive analysis using quantitative research methods with techniques cross sectional. The results of research in the Universe hostel is one form of organizing food that is not looking for profit. As much as 83.4% of the organization of food in the boarding school kitchen has been implemented well. There were 18 students (60%) who had good levels of energy adequacy. Students who have normal nutritional status and acceptability are 16 students (53.3%) out of 30 students. The conclusion of this research is that the implementation of food has been implemented well so that the level of energy sufficiency and nutritional intake of female students living in the boarding school has no problems and those who have normal nutritional intake and acceptability are more than half of all female students living in the boarding school. Keywords: food provision, boarding school, nutritional intake.